Dengue and yellow fever: the anatomy of decline and emergence - Gubler, Duane J. (Henry Stewart Talks, 2010)
Dengue and Yellow Fever virus, are both Flaviviruses, Epidemiology and transmission cycles, History, Effective control, Re-emergence of epidemic dengue as global public health problem, Reasons for emergence, Threat of Yellow Fever as an emerging epidemic disease
Archived at 2020/08/11